1999
DOI: 10.1046/j.1537-2995.1999.39050465.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral or intravenous iron as an adjuvant to autologous blood donation in elective surgery: a randomized, controlled study

Abstract: In non-iron-deficient patients undergoing modest ABD without erythropoietin therapy, neither oral nor i.v. application of iron during the preoperative period enhances the success of preoperative ABD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 24 publications
1
46
0
3
Order By: Relevance
“…For patients subjected to more aggressive phlebotomy (up to 2 units weekly), the endogenous EPO response is more substantial [8][9][10][11]. In one clinical trial [9], a linear-logarithmic relationship was demonstrated between change in hemoglobin level and the endogenous EPO response [12].…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…For patients subjected to more aggressive phlebotomy (up to 2 units weekly), the endogenous EPO response is more substantial [8][9][10][11]. In one clinical trial [9], a linear-logarithmic relationship was demonstrated between change in hemoglobin level and the endogenous EPO response [12].…”
Section: Efficacymentioning
confidence: 99%
“…The erythropoietic response that occurs under these conditions is therefore modest [5]. A summary of prospective, controlled trials of patients undergoing such blood loss via autologous phlebotomy is presented in Table 2 [6][7][8][9][10][11], along with calculated estimates of red blood cell (RBC) volume expansion (erythropoiesis in excess of basal rates). With routine PAD, erythropoiesis of 220-351 ml (11-19% RBC expansion) [6,7], or the equivalent of 1-1.75 blood units, occurs in excess of basal erythropoiesis, which indicates the efficacy of this blood conservation practice.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably related to the fact that both groups of patients that were included in PABD, immediately after blood collection, began with oral iron replacement, while the group that did not give blood did not receive pre-operative iron. According to Weisbach et al [20] for patients without iron deficiency before PABD, if intravenous or oral iron therapy is started it increases the success rate of PABD but does not reduce the need for allogeneic blood transfusions. According to Biesma et al [21] in PABD donors with normal levels of iron, iron compensation has no effect on erythropoiesis and is insufficient to maintain iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…6 Observations in blood donors show that erythropoiesis is only modestly stimulated after phlebotomy and does not improve with oral iron supplementation. 7,8 Furthermore, the degree to which erythropoiesis is stimulated is not dependent on the level of storage iron present. 9 This suggests that iron is not a limiting factor for haemoglobin recovery after acute blood loss in iron-replete individuals.…”
Section: Discussionmentioning
confidence: 99%